Pedestrian crash frequency: Unpacking the effects of contributing factors and racial disparities. (March 2023) - Haddad, Angela J.; Mondal, Aupal; Bhat, Chandra R.; Zhang, Angie; Liao, Madison C.; Macias, Lisa J.; Lee, Min Kyung; Watkins, S. Craig
Highlights: Pedestrian crash counts are modeled. Disparities between majority Black and non-majority Black neighborhoods are examined. Pedestrian crashes are strongly affected by the density of transit stops. Black pedestrians are more likely to be involved in crashes in non-majority Black neighborhoods. Policy and equity implications are identified. Abstract: In this paper, we unpack the magnitude effects of the determinants of pedestrian crashes using a multivariate analysis approach. We consider four sets of exogenous factors that characterize residential neighborhoods as well as potentially affect pedestrian crashes and the racial composition of such crashes: (1) crash risk exposure (CE) attributes, (2) cultural variables, (3) built environment (BE) features, and (4) sociodemographic (SD) factors. Our investigation uses pedestrian crash and related data from the City of Houston, Texas, which we analyze at the spatial Census Block Group (CBG) level. Our results indicate that social resistance considerations (that is, minorities resisting norms as they are perceived as being set by the majority group), density of transit stops, and road design considerations (in particular in and around areas with high land-use diversity) are the three strongest determinants of pedestrian crashes, particularly in CBGs with a majority of the resident population being Black. The findings of this study can enable policymakers and planners to develop more effective countermeasures and interventions to contain the growing number of pedestrian crashes in recent years, as well as racial disparities in pedestrian crashes. Importantly, transportation safety engineers need to work with social scientists and engage with community leaders to build trust before leaping into implementing planning countermeasures and interventions. Issues of social resistance, in particular, need to be kept in mind.